Food and Cultural Traits in Coastal Northern Finnmark in the 14th-19th Centuries - Fjellström, Markus; Eriksson, Gunilla; Lidén, Kerstin Birgitta; Svestad, Asgeir (Norwegian Archaeological Review, 2019)
In this study, we used stable isotope analysis and radiocarbon dating to study diet, mobility and chronology in two late medieval/historical coastal populations in northern Norway. We have shown that the individuals buried at Kirkegårdsøya date between 1331 and 1953 cal AD and had a homogenous marine diet, whereas the individuals buried at Gullholmen had a more heterogeneous diet, consisting of both terrestrial and marine proteins and date between 1661 and 1953 cal AD. We have demonstrated that reindeer protein was not an important part of their diet, and also discussed the importance of correcting for the marine reservoir effect in populations with a coastal subsistence. Our interpretation is that individuals buried at Kirkegårdsøya primarily belonged to a Coastal Sámi community, although Norwegians with a similar diet (and likely comprising a minor population in the area) cannot be ruled out. The more varied diet and mobility at Gullholmen could, as predicted, indicate that these individuals may have had a more diverse cultural affinity.